Nasolabial Angle in Patients with Maxillary Incisor Proclination- A Retrospective study - M, APARNA.; B, NIVETHIGAA; V, RAKSHAGAN (The journal of contemporary issues in business and government, 2021)
Nasolabial angle is a key indicator of facial esthetics and plays an important role in orthodontic diagnosis and treatment planning. Nasolabial angle is formed between a tangent to the lower border of the nose and a line joining the subnasale with the labial portion of the upper lip. Normal range of the nasolabial angle is 90 to 110 degrees.The aim of this study was to evaluate the gender association of various forms of nasolabial angle in patients with the maxillary incisor proclination. A total of six hundred and thirty five patients between the age group of 18 to 30 years were taken into study. Their cases reports were reviewed and retrieved from dental records and the data related to the correlation of nasolabial angle with the proclination of maxillary incisor were retrieved and tabulated. The correlation of nasolabial angle with age and gender distribution of patients with proclination of maxillary incisor was found using chi square test analysis in which P value was < 0.05 and this study is statistically significant.It is thus , important to record the soft tissue details and utilize them during diagnosis and treatment planning ,so that both functional and esthetic harmony could be obtained.